(untitled) (Virginia, U. K., 1999)
Contested issues of ecosystem management provides park rangers, forestry students and personnel with a unique discussion of the premise, goals, and concepts of ecosystem management. You will discover the need for you to maintain and enhance the quality of the environment on a global scale while meeting the current and future needs of an increasing human population. This unique book includes ways to tackle the fundamental causes of environmental degradation so you will be able to respond to the problem and not merely the symptoms.
Keywords: Ecosystem management,Hệ sinh thái; Quản lý